Physico-chemistry, destratification and nutrient budget of a lowland eutrophicated Malaysian reservoir and its limnological implications - Arumugam, P. T.; Furtado, J. I. (Kluwer Academic Publishers, 1980)
Subang Lake (3° 10′N, 101°29′E) is a stratified lowland reservoir with a marked chemocline of some variables that probably contributes to a greater species diversity and vertical layering of plankton communities. Destratification occurs in the reservoir and is probably seasonal. Destratification results in toxic and deoxygenated waters as well as nutrient replenishment from the hypolimnion and could cause sudden mass fish and zooplankton mortality and consequent algal blooms. The nutrient budget study indicates that the reservoir is naturally oligotrophic with phosphate as a limiting factor and the high nutrient loading of the auxiliary water intake from a nearby river, Buloh River, is the cause of eutrophication in the reservoir.